Implementation of the Integration-Interconnection of Introduction to Islamic Studies at the Sociology Study Program of UIN Sunan Kalijaga Yogyakarta - Elvi Tri Astuti Rohmah; Yayan Suryana; Sibawaihi Sibawaihi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This paper discusses the application of interconnection integration in Introduction to Islamic Studies in the Department of Sociology at the State Islamic University of Sunan Kalijaga Yogyakarta. The purpose of this study is to find out how an educator / lecturer in dealing with students who do not have basic Islamic religion at the previous level of education. In addition to applying in learning, interconnection integration is also applied in lecture material. This research uses descriptive qualitative research. Research data obtained from observations, journals, books, and opinions related to the integration of interconnections and Islamic studies. The result of the research is that educators always recommend students to include concrete examples in each material according to the specified approach. In each of the given material themes, an approach is always used, which integrates science and religion. After learning is complete, students are also given the task of writing a resume of at least two paragraphs which contains the core of the discussion in each meeting. Integration of interconnections is important to always be developed in any type of science, in order to produce updates in the future.